Requirements to assess feasibility of phase 0 trials during major abdominal surgery: variability of PARP activity - Heitz, Florian; Rochon, Justine (Clinical cancer research, 2012)
Purpose: The aim of this study was to evaluate the feasibility of phase 0 trials in the setting of a routine surgical procedure. Logistic considerations, tissue sampling and tissue handling, and variability of a biomarker during surgery, in here PARP, were evaluated. Experimental Design: Patients with highly suspicious or proven diagnosis of advanced ovarian cancer, planned for debulking surgery were asked to allow sequential tumor biopsies during surgery. Biopsies were frozen immediately and PARP activity was measured subsequently. Results: Baseline biopsies were obtained from eight patients after a median time of 88 minutes (minimum of 50 to maximum of 123 minutes). Second and third biopsies were obtained after a median of 60 (32-96) and 101 (79-130) minutes, respectively. Mean tumor load was 44% (5%-100%), with a cellular viability of 98% (85%-100%). Median baseline PARP activity was 1035 pg/mL (range, 429-2663 pg/mL). The observed interpatient variability at baseline was large: SD was 0.59 after natural logarithm transformation. Conclusions: Conducting phase 0 trials during surgery seems to be feasible in terms of logistic considerations. In preparation of a phase 0 trial during surgery, a feasibility study like this should be conducted to rule out major interactions of the surgical intervention with respect to the targeted biomarker.
Gesehen am 20.04.2018